Defect-induced photoluminescence of powdered silica glass - Pizani, P. S.; Joya, M. R.; Pontes, F. M. [UNESP]; Santos, L. P S; Godinho, M.; Leite, E. R.; Longo, Elson [UNESP] (Trans Tech Publications, 2008)
Visible photoluminescence was generated in standard soda-lime-silica glass powder, mechanically milled in a high-energy attrition mill. The broad emission band maximum shows a linear dependence on the exciting wavelength, suggesting the possibility to tune the PL emission. The photoluminescence was attributed to defect generation related to unsatisfied chemical bonds due to the high surface area. Raman scattering and ultraviolet-visible optical reflectance measurements corroborate this assertion. Transmission electron microscopy measurements indicate that the powder is composed by nanocrystallites with about 10-20 nanometers immersed in an amorphous media.
Keywords: Attrition mill; Photoluminescence; Silica glass; Surface defects; Emission band; High-energy attrition mill; Optical reflectance measurements; Crystal defects; Mechanical alloying; Powder metallurgy; Reflectometers; Transmission electron microscopy; Fused silica